ECLOGITISATION OF GABBROIC ROCKS: REDISTRIBUTION OF TRACE ELEMENTS AND Zr IN RUTILE THERMOMETRY IN AN EO-ALPINE SUBDUCTION ZONE (EASTERN ALPS) - Miller C.; Konzett J.; Zanetti A.; Thöni M. (My University, 2007)
The investigation of eclogites and a precursor gabbro from the Austroalpine basement domains Koralpe, Saualpe and Pohorje shows that these mafic rocks are similar to oceanic gabbros that were derived from a depleted mantle source. The chemical variations of the eclogites are related to differences in the magmatic history of the precursor rocks and to seawater alteration. The trace element composition of the rocks has not changed significantly during the gabbro to eclogite transformation because trace elements are redistributed among the newly formed high-pressure major and accessory minerals. As other recent studies indicate, incompatible trace elements are predominantly hosted in zoisite/clinozoisite (Sr, Pb, U, Th, LREE), apatite (Sr, Pb, REE), phengite (Cs, Rb, Ba), garnet (Y, HREE, Sc), rutile (Ti, Nb, Ta) and zircon (Zr, Hf) at eclogite-facies conditions. Omphacite hosts most of the Li in addition to some Sr and major amounts of Sc and V. This argues against significant liberation of LILE and LREE during subduction-related dehydration or fluid infiltration of these mafic rocks.
Keywords: EASTERN ALPS; ECLOGITE; RUTILE THERMOMETRY; SUBDUCTION; TRACE ELEMENTS